Structures Mobilities and Communication in the Argentine Patagonia, Young People (Revista LIDER, 2018)
Understanding that the mobilities of subjects across geographical spaces are traversed by relationships and articulations of power, we choose to speak of structured mobilities. These physical mobilities, as well as virtual mobilities, as a result of changes in communications technology and their slow incorporation into marginalized territories, are part of the youthful paths of Ñorquin Co and Cushamen, small towns located in the northwest of Argentine Patagonia. The unfolding of these trajectories challenges and transforms the spaces themselves, giving new and different meanings to rurality